Peningkatan Hasil Belajar Lari Sprint 30 Meter Melalui Modifikasi Permainan "Bentengan" di Sekolah Dasar - Fasisal Asrori; Adi Suriatno; Nune Wire Panji Sakti (Discourse of Physical Education, 2022)
Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar lari sprint 30 meter melalui modifikasi permainan bentengan. Metode penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK). Penelitian ini dilaksanakan dalam dua siklus, dengan tiap siklus terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV Madrassah Ibtidaiyah At-Tahzib Desa Kekait, yang berjumlah 20 orang berjenis kelamin laki-laki 12 orang dan berjenis kelamin perempuan 8 orang. Teknik pengumpulan data melalui tes kemampuan lari sprint 30 meter dan observasi dari proses kegiatan pembelajaran. Validitas data menggunakan teknik triangulasi. Analisis data menggunakan teknik deskriptif dengan menggunakan teknik prosentase untuk melihat kecenderungan yang terjadi dalam kegiatan pembelajaran. Kondisi awal sebelum dilakukan PTK, siswa yang tuntas belajar lari sprint 30 meter hanya 5 siswa, meningkat menjadi 14 siswa pada siklus I (ketuntasan= 65%), dan meningkat kembali meningkat menjadi 19 siswa pada siklus II (ketuntasan= 95%). Modifikasi permainan bentengan memberi kontribusi yang signifikat terhadap peningkatan hasil lari sprint 30 meter. Simpulan penelitian ini menunjukkan bahwa modifikasi permainan bentengan dapat meningkatkan hasil belajar lari sprint 30 meter pada siswa kelas IV Madrassah Ibtidaiyah At-Tahzib Desa Kekait. Improving Learning Outcomes of 30 Meter Sprint Running Through Modification of the Game "Bentengan” in Elementary Schools Abstract This study aims to determine the increase in learning outcomes for the 30 meter sprint through the modification of the game "Bentengan". This research method uses Classroom Action Research. This research was conducted in two cycles, with each cycle consisting of planning, implementing actions, observing, and reflecting. The research subjects were fourth grade students of Madrassah Ibtidaiyah At-Tahzib, Kekait Village, which consisted of 20 students, 12 male and 8 female. The data collection technique was through a 30 meter sprint sprint ability test and observation of the learning activity process. Data validity using triangulation technique. Data analysis used descriptive techniques using percentage techniques to see trends that occurred in learning activities. The initial condition was that before the action research was carried out, only 5 students had completed learning to run the 30 meter sprint. In the first cycle increased to 14 students. Cycle II increased to 19 students. The game modification "Bentengan" made a significant contribution to the improvement of the 30-meter sprint result. The conclusions of this study indicate that the modification of the game "Bentengan" can improve the learning outcomes of the 30-meter sprint in fourth grade students of Madrassah Ibtidaiyah At-Tahzib Kekait Village. The achievement of completeness in learning the 30 meter sprint from the initial condition to the first cycle is 40%. From the first cycle to the second cycle by 30%. The improvement in overall learning outcomes from the initial conditions to the second cycle is 70%.